A Systematic Review of the Relationship between Plastic Surgery and the Medical Industry - Clapham, Philip J. (Plast Reconstr Surg, 2010)
BACKGROUND: The nature and extent of medicine’s relationship with the medical industry is currently a heated issue in medicine. Although the ethical implications of this relationship have been widely discussed in medical journals and the popular media, it is unknown how the current interest in industry issues has affected Plastic Surgery. The aim of this systematic review was to characterize the literature of the past two decades that examines Plastic Surgery’s relationship with the medical industry. METHODS: Three medical databases were searched using Plastic Surgery and industry-related search terms. The quality of selected articles was assessed by two reviewers. The specific data abstracted included the venue of the industry interaction discussed within the article: (1) physician education programs, (2) research partnerships, and (3) clinical settings. Within each of these categories, a comprehensive taxonomy was created to categorize the thematic content of the articles’ discussion. RESULTS: Of the 465 articles gleaned by the search, 21 met the inclusion and exclusion criteria and were included in the final review. All 21 articles were of a review or editorial-type nature and the majority (57%) discussed the nature or effects of industry’s presence within the clinical setting. CONCLUSION: This systematic review revealed the literature’s cursory analysis of Plastic Surgery’s relationship with the medical industry. This project highlighted the need for Plastic Surgery to examine the ethical implications of industry’s support and engagement within the field. Improving this literature is necessary for plastic surgeons to understand and adhere to current standards on acceptable practices.